IMPLEMENTATION OF THE MUHADHOROH ACTIVITY TO BUILD STUDENTS’ SELF-CONFIDENCE AT MTS ISLAMIYAH BUMI AGUNG, OKI - Pipit Ridiana; Yuniar Yuniar; Yulia Tri Samiha (Jurnal Konseling Pendidikan Islam, 2026)
This research employed descriptive qualitative methods using interviews, observation, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation techniques and sources. The results of this study are that the implementation of muhadhoroh activities in strengthening student self-confidence at MTs Islamiyah Bumi Agung OKI runs effectively through the implementation of aspects of direction, coordination, motivation and communication. Through clear direction, helping students understand their tasks, good coordination between the supervisors and students makes muhadhoroh activities more organized, open communication also facilitates the delivery of information, and the motivation provided is able to increase student enthusiasm and self-confidence. Meanwhile, muhadhoroh activities also have a positive impact in strengthening student self-confidence, this is proven by the increase in student self-confidence after participating in muhadhoroh activities. These muhadhoroh activities not only produce students who are academically intelligent, but also have Islamic morals and personalities. In the psychological aspect, students become braver, able to control fear, and have a stronger belief in their abilities. From the social aspect, muhadhoroh activities can improve the ability to interact, cooperate, and appear confident in front of others. Furthermore, the spiritual aspect, this activity can foster discipline in worship, good morals, and motivate students to behave positively. Meanwhile, academically, it demonstrated improvements in communication skills, structured thinking skills, and encouraged active student participation in learning.